Poverty-environment dividends of rural community enterprises: insights from a cross-sectoral study in Latin America and the Caribbean - Stoian, D.; Donovan, J. (CATIE, Turrialba (Costa Rica), 2021)
21 páginas, 7 tablas, 6 ref.